Decision Support System in Managerial Decision Making: A Comparative Study Between Public and Private Sectors in Malaysia - Mohamad Noor, Noor Maizura (1997)
Nowadays, computers are useful tools for managers whether top manager, middle manager or lower manager in any organisation, and information is a vital asset in every modern organisation. So, computers and information are widely used in any purpose of applications. Decision support system (DSS) is one of the computer-based information systems that provides a flexible tool for analysis and also help managers in semi-structured decision making tasks. This study was done to evaluate the usage of DSS and to make comparison between the public and the private sectors in managerial decision making. Comparisons were made based on the seven hypotheses of the study in which management in the private sector has more concern in using DSS than management in the public sector. Regarding the above hypotheses, the study emphasised on the understanding of the usage and current status of DSS in Malaysia, managerial perception, attitudes towards DSS software products, problems and implementation strategies of DSS in the management. Respondents of the study were the middle level managers. Questionnaires were distributed to the selected organisations in Klang Valley. Based on this study, it could be concluded that there were no significant differences between the public and private sectors in terms of experience, effect of DSS use, attitudes towards DSS software products, satisfaction with DSS, problems with DSS use, and implementation strategies. However, there was a significant difference between the public and private sectors in terms of the frequency of using DSS. The public sector tended to irregularly use DSS in their decision making whereas private sector used DSS systematically. Many of the respondents have yet to use DSS because of the lack of knowledge about DSS and not enough support from the top management. Top management must make the new technology available for their employees to use with the necessary hardware, software and DSS prototypes. The adoption of DSS would encourage users to experiment with new ways of working to improve decision making and increase productivity. Overall satisfaction can be fostered by applying DSS to less structured tasks which are formed by users with favourable attitude towards DSS.